Pembelajaran Sastra Berbasis Blended Learning - Prawoto, Eko Cahyo; Pramulia, Pana (Universitas Nusantara PGRI Kediri, 2019)
Blended learning is one of the learning models applied in universities as an improvement in the quality of learning. Blended learning is a blend of two learning models, namely face-to-face learning and online learning/e-learning. Blended learning is used to stimulate and foster learning motivation for students, it is necessary to innovate and create more interesting media. Learning media that can be used in blended learning, namely flipbook software and autoplay, through the two software instructors can create learning media through a combination of learning material in pdf, video (mp4), image (jpeg), ppt (pdf) and so on. Learning media that have been made uploaded in the classroom (google classroom) at the beginning of the lecture. Through google classroom, students can download all learning media. With learning media that have been downloaded, students can learn more innovatively. In the media, the material presented is related to literacy learning. Blended learning-based learning models can improve literacy learning outcomes in Unipa Surabaya PBSI students in Literature Appreciation courses. The increase was due to the tendency of students to be more active, innovative, creative, and enthusiastic in independent learning, and in working on assignments given as evaluations in lectures with the learning media that had been provided.